Akuntabilitas Dan Pengelolaan Keuangan Di Masjid Melalui Pendekatan Fenomenologi : (Studi Kasus Masjid Agung Sidikalang) - Abidin Alimuddin Sihotang; Mustafa Kamal Rokan; Arnida Wahyuni Lubis (Jurnal Riset Akuntansi, 2024)
This study shows that the importance of accountability in financial reports. The goal to be achieved is to look at the financial statements at the Great Sidikalang mosque whether it is in accordance or not in accordance with applicable standards. This research uses descriptive qualitative with a phenomenological approach. The phenomenological approach is used to understand in depth the activities to finance that exist in the Great Sidikalang mosque. This research obtained an explanation of accountability both for fellow humans and accountability to Allah SWT in accordance with the understanding and reality experienced by the administrators. In connection with the financial statements, the Sidikalang Great Mosque still does not fulfill the components of the financial statements in accordance with PSAK No. 45. The Sidikalang Great Mosque only presents reports in a simple manner due to limited human resources. Therefore, researchers construct financial reports in accordance with PSAK No. 45 from the data obtained by researchers